Study of the Functional State of the Proximal Renal Tubules in Patients with Asymptomatic Chronic Heart Failure in Dyslipidemia and its Correction with Simvastatin Treatment - V. Yu. Kopylov (Рациональная фармакотерапия в кардиологии)
Aim. To study indicators of epithelial dysfunction in the proximal renal tubules by determining the activity of organ-specific enzymes neutral α-glucosidase (NAG) and L-alanine aminopeptidase (LAAP), in patients with the initial stage of chronic heart failure in dyslipidemia, and the possibility of reducing with simvastatin.Material and methods. The study involved 90 subjects, who were divided into control and main groups. The control group consisted of 30 practically healthy individuals, the main group was divided into 2 subgroups: patients with stage I chronic heart failure (CHF) without type 2 diabetes mellitus (DM2) and patients with CHF with DM2. Patients of each of the main subgroups received simvastatin 20-40 mg/day in addition to treatment of the main pathology. The main group included patients with a total serum cholesterol level of more than 6.0 mmol/l, a BMI level of more than 30 kg/m2, and who had not previously taken statins. The exclusion criterion was a violation of the filtration capacity of the kidneys and the presence of gross dysfunction of organs and systems of the body. The functional state of the proximal renal tubules was assessed by the concentration of NAG and LAAP in dialized urine.Results. Initially, the level of activity of renal enzymes in representatives of both major subgroups is higher than the group of practically healthy individuals. Taking simvastatin in the CHF without DM2 subgroup does not cause an increase in enzyme activity throughout the entire observation period, either at a daily dosage of 20 mg (NAG - 12.36±2.65 ncat/1 14.1±5.23 ncat/1 and after 3 and 6 months, LAAP - 9.4±1.62 and 11.2±2.99 ncat/1 after 3 and 6 months), or at a dosage of 40 mg/day (NAG - 30.47±3.85 and 26.2±6.75 ncat/1 after 3 and 6 months; LAAP -17.3±3.56 and 19.58±3.83 ncat/1 after 3 and 6 months). Taking simvastatin 20 mg/day in patients with CHF with DM 2 causes an increase in the NAG activity: 26.68±6.03 and 34.57±9.73 ncat/1 after 3 and 6 months). Taking simvastatin 40 mg/day increase both enzyme activity: NAG -34.3±8.7 and 46.94±9.02 ncat/1 after 3 and 6 months, LAAP - 17.08±5.81 and 22.41±4.89 ncat/1 after 3 and 6 months).Conclusion. The appointment of simvastatin in patients with dyslipidemia on the background of obesity is permissible in order to normalize lipid metabolism. Safe for the functional state of the proximal renal tubules, long-term administration of simvastatin, within the limits of medium-therapeutic dosages, is possible for patients without type 2 diabetes. Long-term use of simvastatin in patients with dyslipidemia on the background of type 2 diabetes mellitus has a negative effect on the epithelium of the proximal renal tubules, in the form of an increase in the activity of renal organ-specific enzymes, which indicates an increased dystrophy of the epithelium.